Microcirculatory abnormalities in patients with severe influenza A (H1N1) infection - Salgado, Diamantino R. (Can J Anaesth, 2010)
PURPOSE: This study was designed to evaluate the degree of microcirculatory abnormalities in patients with severe influenza A (H1N1) infection. METHODS: We assessed the sublingual microcirculation in seven consecutive patients with acute lung injury related to influenza A (H1N1) infection. The evaluation was carried out using sidestream dark field (SDF) imaging within the first 96 hr after the patients were admitted to the intensive care unit. Thenar oxygen saturation (StO(2)) was also measured with near-infrared spectroscopy (NIRS) during a vascular occlusion test. In addition, the Lung Injury Score (LIS) and the APACHE II and SOFA scores were recorded. RESULTS: All patients received invasive mechanical ventilation and at least one of the following adjuvant therapies: inhaled nitric oxide (n = 4), extracorporeal membrane oxygenation (n = 1), prone position (n = 4), recruitment maneuver (n = 3), and hydrocortisone 50 mg·hr(−6) (n = 6). The median time from admission to microcirculatory assessment was 21 hr. Three patients had bacterial superinfection. The median LIS and PaO(2)/F(i)O(2) were 2.5 (2.25-3.25) and 178 (158-212), respectively. Three subjects were treated with norepinephrine. During a vascular occlusion test, the microcirculation was moderately to severely compromised with a NIRS ascending slope of 2.39%·sec(−1) (1.75-2.67%·sec(−1)), 66% (60-86%) of perfused small vessels in the sublingual microcirculation, and a microvascular flow index of 1.9 (1.3-2.6). The degree of microcirculatory abnormalities detected by the NIRS and SDF imaging techniques was correlated with the severity of the disease, as reflected by the SOFA and APACHE II scores. CONCLUSIONS: The microcirculation as assessed by SDF imaging and NIRS techniques was compromised in patients with acute respiratory distress syndrome (ARDS) and influenza A (H1N1) infection.